The Metabolic Response of Skeletal Muscle to Endurance Exercise Is Modified by the ACE-I/D Gene Polymorphism and Training State - Valdivieso, Paola; Vaughan, David; Laczko, Endre; Brogioli, Michael; Waldron, Sarah; Rittweger, Jörn; Flück, Martin (Frontiers in Physiology, 2017)
The insertion/deletion polymorphism in the gene for the regulator of vascular tone, angiotensin-converting enzyme (ACE), is the prototype of a genetic influence on physical fitness and this involves an influence on capillary supply lines and dependent aerobic metabolism in skeletal muscle. The respective interaction of ACE-I/D genotype and training status on local metabolic and angiogenic reactions in exercised muscle is not known. Towards this end we characterized the metabolomic and angiogenic response in knee extensor muscle, m. vastus lateralis, in 18 untrained and 34 endurance-trained (physically active, VO2max>50 mL min-1 kg-1) white British men to an exhaustive bout of one-legged cycling exercise. We hypothesized that training status and ACE-I/D genotype affect supply-related muscle characteristics of exercise performance in correspondence to ACE expression and angiotensin 2 levels. ACE-I/D genotype and training status developed an interaction effect on the cross-sectional area (CSA) of m. vastus lateralis and mean CSA of slow type fibers, which correlated with peak power output (r≥0.44). Genotype x training interactions in muscle also resolved for exercise-induced alterations of 22 metabolites, 8 lipids, glycogen concentration (p=0.016), ACE transcript levels (p=0.037), and by trend for the pro-angiogenic factor tenascin-C post exercise (p=0.064). Capillary density (p=0.001), capillary-to-fiber ratio (p=0.010), systolic blood pressure (p=0.014), and exercise-induced alterations in the pro-angiogenic protein VEGF (p=0.043) depended on the ACE-I/D genotype alone. Our observations indicate that variability in aerobic performance in the studied subjects was in part reflected by an ACE-I/D-genotype-modulated metabolic phenotype of a major locomotor muscle. Repeated endurance exercise appeared to override this genetic influence in skeletal muscle by altering the ACE-related metabolic response and molecular aspects of the angiogenic response to endurance exercise.